Sulforaphane in experimental hypertension - Ali Banigesh; Vijitha Senanayake; Salma Bukhatwa; Bernhard Juurlink (Libyan International Medical University Journal)
Background: Hypertension is defined as a failure to achieve a blood pressure (BP) target – smaller than 140/90 mmHg. The worldwide burden of hypertension has been associated with globally increased rates of death and disability. There is increasing evidence of strong relation between hypertension and oxidative stress, where either increased oxidative stress or depressed antioxidant level may lead to hypertension. Using stroke-prone spontaneously hypertensive rats (SHRSP) rats, previous studies in our laboratory have shown that broccoli sprouts (high in sulforaphane, a phase-2 protein inducer) attenuate BP and inflammation. Objectives: The question this study addressed was whether sulforaphane (a potent phase-2 protein inducer) can attenuate hypertension in the experimental model using the stroke-prone spontaneously hypertensive rats (SHRsp). Materials and Methods: Sulforaphane (LKT Laboratories) or vehicle was orally gavaged to SHRsp or Sprague–Dawley rats (SD) daily for 15 weeks. The body weight and BP were determined weekly, using a standard tail-cuff BP measurement. Tissues such as hearts and kidneys were collected, weighed, and stored under −80°C for further analysis. Results: When compared to BP in SHRsp control rats (179.9 ± 4.32), sulforaphane significantly reduced BP to 157 ± 5.21 (10 μmol/kg body weight), 136.57 ± 1.96 (20 μmol/kg body weight), and 129.33 ± 6.10 (5 μmol/kg body weight), respectively, in SHRsp rats. Conclusion: Administration of sulforaphane, a potent phase-2 enzyme inducer, daily for more than 3 months, significantly improves BP in SHRsp rats, but it did not have any effects on normotensive rats – SD.